2012
DOI: 10.1111/j.1742-481x.2011.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological measurements of tissue health; implications for clinical practice

Abstract: Pressure mapping alone insufficiently describes tissue health. Comprehensive, quantitative non invasive assessment is crucial. Interface pressures (IPs) and transcutaneous blood gas levels [transcutaneous tissue oxygen (T(c) PO(2) )] were simultaneously assessed over both ischia and the sacrum to investigate the hypotheses: (i) tissue oxygenation decreases with sustained applied pressure; (ii) tissue oxygen and IP are inversely correlated in loaded soft tissues; (iii) multisite assessments are unnecessary beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This result was also shown by Kim et al (2012) who reported values for interfaces pressures that are similar in magnitude and distribution to the present study (median = 46, range 27-84 mm Hg). In addition, their evaluation of transcutaneous tissue oxygen values at the sacrum was reported to remain stable during 20 minutes of static supine lying, with mean values of TcPO2 between 31 and 37 mm Hg.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result was also shown by Kim et al (2012) who reported values for interfaces pressures that are similar in magnitude and distribution to the present study (median = 46, range 27-84 mm Hg). In addition, their evaluation of transcutaneous tissue oxygen values at the sacrum was reported to remain stable during 20 minutes of static supine lying, with mean values of TcPO2 between 31 and 37 mm Hg.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is well established that interface pressures alone do not alert the clinician to risk of pressure ulcers and the imprecise relationship between pressure magnitude and duration limits the predictive or prognostic value of the measured parameter (Reenalda et al, 2009). Accordingly, much research has utilised measures of tissue viability, often in the form of transcutaneous gas monitoring, to examine the tissue response to mechanical loads (Chai and Bader, 2013;Kim et al, 2012;Makhsous et al, 2007). These studies have shown distinct changes in tissue oxygen (TcPO 2 ) and carbon dioxide (TcPCO 2 ) tensions when measured at differing skin sites subjected to representative external pressures (Knight et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They found no difference between time point measurements and no significant correlations between interface pressure and TcPO 2 . However, they did find some asymmetries in measures taken from the left and right side of the ischium highlighting that multiple sites of evaluation should be taken (Kim et al, 2012). There are however, some questions as to whether 20 minutes is sufficient to evaluate physiological response to pressure given the known association of time.…”
Section: Combining Measuresmentioning
confidence: 98%
“…A recent study was conducted by Kim et al (2012), where interface pressures and transcutaneous blood gas measurements were taken during sitting and lying. Here they took measurements every 5 minutes for a total of 20 minutes.…”
Section: Combining Measuresmentioning
confidence: 99%
“…Detailed spectral analysis also reveals component contributions to blood flow [1617]. LDF blood flow assessment combined with T c PO 2 measurement can thus reveal tissue health information that cannot be provided by IP measurement alone [18–20]. …”
Section: Introductionmentioning
confidence: 99%